Causes and factors associated with neonatal mortality in Creole sheep flocks - Espinoza-Montes, Francisco (2022)
The study was carried out to identify the causes and factors associated with neonatal lamb mortality in Creole sheep flocks in extensive rearing system. Three farms located in the grasslands of the peasant community of Quero, province of Jauja, Peru, located at altitudes between 3972 and 4430 m were selected. Flocks were visited once every two weeks to collect information on mortality. The neonatal mortality rate at the end of the lambing season was 21.2%. The causes of mortality were in order of frequency: pneumonia, starvation, dystocia, diarrhoea and predation. The highest mortality rate occurred within 48 hours of parturition (71.4%). Lambs born to ewes with a body condition score (BCS) <2 were more likely to die than those born to ewes with better BCS (OR = 7.42). Moreover, lambs with >2 kg birth weight (OR = 3.52) and those born in farm C (OR = 3.42) were three times more likely to die than the heaviest lambs or those born in farms A and B, respectively.